(untitled) (NAU Journal of Library and Information Science, 2023)
The study was focused on how to developed librarians’ knowledge and ICT skills for effective library services and national integration. Three research questions guided the study. The study was conducted in Anambra State, Nigeria. Population of the study comprised 208 librarians (49 males and 159 females) in 16 libraries in Anambra State. There was no sampling as the population was small and manageable. Instrument for data collection was a questionnaire titled ‘Librarians Knowledge and Skill of ICT for Effective Library Services and National Integration’. Data collected was analysed using mean score rating. The findings of the study revealed that librarians need ICT skills to develop web-based applications; access and deliver e-mails, e-resources and databases, and so on. It was also revealed that librarians in Anambra State possessed ICT skills such as sending e-mails; Internet searching; typing and printing documents; providing information literacy education, amongst others. Furthermore, the study revealed that librarians’ knowledge and ICT skill could be developed through sharing of ideas with more knowledgeable librarians; brainstorming with computer operators working in the LIS Department; enforcing the use of e-mail services in contacting librarians and online publication of articles in high impact journals. It was recommended that the NLA should increase the number of professional development programmes such as conferences and seminars to enable librarians acquire new ideas and learn best practices.